Identification of new candidate genes for the hereditary predisposition to uveal melanoma: IGCMU trial - Godiveau, Mélanie; Ginzac, Angeline; Bidet, Yannick; Ponelle-Chachuat, Flora; Privat, Maud; Durando, Xavier; Cavaillé, Mathias; Lepage, Mathis (Frontiers in Oncology, 2025)
IntroductionUveal melanoma (UM) is a rare ocular cancer. While germline mutations in genes such as BAP1 and MBD4 account for approximately 20% of familial UM cases, the hereditary factors underlying the remaining cases remain unknown. Epidemiological studies have suggested an increased risk of prostate cancer, thyroid cancer, and leukemia among patients with UM, indicating potential unidentified genetic predispositions. This study aims to identify new candidate genes associated with a hereditary predisposition to UM.MethodsThis single-center study, conducted at Centre Jean Perrin, will involve the exome sequencing of 50 patients with UM who do not harbor known pathogenic variants in the BAP1 or MBD4 genes. The primary objective is to identify novel candidate genes associated with hereditary cancer predisposition among UM patients. A several-step-bioinformatic analysis will be conducted to identify the genes of interest. A secondary objective is to explore genes known to be involved in predisposition to other cancers, already described in the occurrence of uveal melanoma, but where an association has not been fully established yet. The study has begun in October 2024, with patient recruitment lasting 12 months. No follow-up period is planned, but the duration of the genetic analyses is estimated at six months, with the final study report expected by October 2026.DiscussionThe identification of novel hereditary predisposition genes for UM could significantly enhance genetic counselling and surveillance strategies for families affected. This study could also contribute to a better understanding of the genetic landscape of UM, potentially leading to more personalized and effective options for its detection.Trial registrationClinicalTrials.gov, identifier NCT06550674, registered in August 2024. Protocol: version 1.0, January 18th, 2024.